Proceedings of the 3rd Annual Conference on Task Models and Diagrams - TAMODIA '04 2004
DOI: 10.1145/1045446.1045458
|View full text |Cite
|
Sign up to set email alerts
|

Focus-based design of mixed reality systems

Abstract: Currently very few techniques are available to support the design of Augmented and Mixed Reality (MR) systems. Task elicitation is more complex for MR systems than for traditional information systems. Having multiple sources of information and two worlds of interaction (real and virtual) involves making choices about what to attend to and when. Interaction based on traditional input and output devices is not effective in a mixed scenario. It distracts the user from the task at hand and may create a severe cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…As wrist-worn displays and HMDs also help to accomplish similar tasks, we investigate which display modality works best when users need to split their attention. Trevisan et al showed that when real and virtual worlds interact, designers must focus a user's attention on one or the other [46], pointing out that the ability to focus is affected by UI design. We investigate intentional splitting of attention as a part of gameplay, making decisions about where to focus a game mechanic.…”
Section: Splitting Attentionmentioning
confidence: 99%
“…As wrist-worn displays and HMDs also help to accomplish similar tasks, we investigate which display modality works best when users need to split their attention. Trevisan et al showed that when real and virtual worlds interact, designers must focus a user's attention on one or the other [46], pointing out that the ability to focus is affected by UI design. We investigate intentional splitting of attention as a part of gameplay, making decisions about where to focus a game mechanic.…”
Section: Splitting Attentionmentioning
confidence: 99%
“…As pointed out by Trevisan et al (2004) it is more difficult to model tasks in the context of two worlds of interaction (real and virtual) and multiple sources of information. They suggested an integration of several notations in order to express the specific task characteristics in AR.…”
mentioning
confidence: 99%